2021
DOI: 10.3390/ani11010072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multi-Species Direct-Fed Microbial Products on Ruminal Metatranscriptome and Carboxyl-Metabolome of Beef Steers

Abstract: We examined the effects of two direct-fed microbial (DFM) products containing multiple microbial species and their fermentation products on ruminal metatranscriptome and carboxyl-metabolome of beef steers. Nine ruminally-cannulated Holstein steers were assigned to 3 treatments arranged in a 3 × 3 Latin square design with three 21-d periods. Dietary treatments were (1) Control (CON; basal diet without additive), (2) Commence (PROB; basal diet plus 19 g/d of Commence), and (3) RX3 (SYNB; basal diet plus 28 g/d o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Prevotella ruminicola [ 49 ] and Ruminococcus spp. [ 50 , 51 ] are also prevalent fiber degraders within the rumen. Our findings raise the possibility that expression of ARGs could impact the relative contribution of these species to ruminal fiber and starch digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella ruminicola [ 49 ] and Ruminococcus spp. [ 50 , 51 ] are also prevalent fiber degraders within the rumen. Our findings raise the possibility that expression of ARGs could impact the relative contribution of these species to ruminal fiber and starch digestion.…”
Section: Discussionmentioning
confidence: 99%
“…The PA concentration used in this study was based on the reported serum concentrations of fatty acids during the early postpartum period ( Rukkwamsuk et al., 1999 ) and the NaP concentrations used were also based on previously reported data ( Donkin and Armentano, 1995 ; McCoun et al., 2021 ). Cells were maintained in RPMI 1640 basic medium containing 2% BSA and treated with different concentrations of PA (0, 100, 200, or 400 μM) and NaP (0, 1, 2.5, or 5 mM), alone or in combination, for 12 h.…”
Section: Methodsmentioning
confidence: 99%